In Vivo Assessment of Antioxidants and Antihyperglycemic Effect of Barleria cristata leaves in Streptozotocin- Induced Diabetic Rats - Rajasekaran, Narmadha; Duraisamy, Gomathi; Manokaran, Kalaiselvi; Kanakasapathi, Devaki (International Journal of Applied Sciences and Biotechnology, 2014)
Objective: Many new bioactive drugs isolated from plants having hypoglycaemic effects showed anti diabetic activity equal and sometimes even more potent than known oral hypoglycaemic agents. In this present study, designed to evaluate antihyperglycermic and antioxidants effect on ethanolic leaf extracts Barleria cristata (EtBc) in streptozotocin-induced diabetic rats at dose level 400mg/kg body weight for the treatment of 45 days. Method and materials: The experimental rats were randomly divided into five groups as a control, streptozotocin induced with diabetes (45mg/kg bw) without any treatment, treated with standard drug glibenclamide (1.25 mg/kg bw), EtBc (400 mg/kg bw) in diabetic induced rats and treated with EtBc alone without diabetic rats. At the end of 45th day animals were sacrificed, collect the serum, liver, kidney and pancreas for estimate the glucose, insulin, C-peptide, glycosylated hemoglobin, hemoglobin in serum, protein, enzymatic and nonenzymatic antioxidants and lipid peroxidation in tissues. Results: After the administration of EtBc, blood glucose levels were showed significantly reduction (P